Prediction of enophthalmos by computed tomography after 'blow out' orbital fracture. Issue 8 (August 1994) - Whitehouse, R W; Batterbury, M; Jackson, A; Noble, J L
Abstract : In 11 patients with blow out fracture of the orbit, measurement of orbital volume using computed tomography (CT) more than 20 days after injury correlated well with enophthalmos measured from the same scans (r = 0.87, p < 0.001, SEE 0.63 mm), with a 1 cm3 increase in orbital volume causing 0.8 mm of enophthalmos. This confirms the cause of enophthalmos after blow out fracture to be increase in orbital volume rather than fat atrophy or fibrosis. In a further 25 patients scanned within 20 days of injury the degree of enophthalmos was less marked than would be predicted from the orbital volume measurement. This was probably because of the presence of oedema, haemorrhage, or both behind the globe which would prevent immediate development of enophthalmos. CT measurement of orbital volume within 20 days of injury may predict the final degree of enophthalmos and identify those patients at risk of late enophthalmos, allowing appropriate early surgical intervention.